Digital Communication and the Rise of Online Activism - Phillips, Cory (Journal of Communication, 2024)
Purpose: The general objective of the study was to explore digital communication and the rise of online activism. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to digital communication and the rise of online activism. Preliminary empirical review revealed that digital communication had fundamentally transformed social and political activism, enabling rapid mobilization and broad dissemination of information. This shift democratized participation, allowing diverse voices to contribute to movements. However, the study also highlighted challenges such as the ephemeral nature of online engagement and the risks of reliance on centralized platforms. Despite these challenges, the potential for digital activism to drive meaningful change was evident, provided that movements could sustain real-world action and build resilient networks. Unique Contribution to Theory, Practice and Policy: The Network Society Theory, Collective Action Theory and Framing Theory may be used to anchor future studies on digital communication and the rise of online activism. The study concluded that the integration of digital communication in activism required updates to theoretical frameworks to reflect the dynamic nature of online platforms. Practically, it recommended that activists enhance their digital strategies, prioritize digital literacy and security, and create engaging content to sustain participation. Policy-wise, it emphasized the need for regulations that protect online activism while preventing misinformation. Educational institutions were urged to incorporate digital activism into their curricula. Collaborative efforts among activists, tech developers, and policymakers were highlighted as essential for developing supportive technologies. Lastly, the study called for ongoing research to understand the long-term impacts and ethical implications of digital activism, noting its evolving influence on social and political landscapes.